Quality of Maize Silage After Using Meat Bone Meal as a Phosphorus Fertilizer in a Field Experiment - Anna Nogalska; Marta Borsuk-Stanulewicz; Cezary Purwin; Zenon Nogalski (Applied Sciences)
The aim of this study is to determine the effects of increasing doses of meat and bone meal (MBM) and the year of the experiment on the feed value of maize silage. A three-year field experiment with silage maize was conducted. The following treatments were established: (1) zero-fert (no fertilization); (2) inorganic nitrogen (N), phosphorus (P), and potassium (K); (3) 1.0 t∙ha−1 MBM; (4) 1.5 t∙ha−1 MBM; (5) 2.0 t∙ha−1 MBM. Both N and K were applied at constant rates, while P was applied at increasing rates: 0.0, 45, 68, and 90 kg∙ha−1. Replacing conventional P fertilizer and, partially, N fertilizer with MBM in silage maize cultivation had a positive influence on the ensiled herbage, compared with the zero-fert treatment. The fermentation parameters and feed value of silage made from maize fertilized with MBM were comparable with the parameters of maize fertilized with inorganic NPK fertilizers. In turn, the content of crude protein (CP) and protein digested in the small intestine when energy is limiting (PDIE) was highest in the silage made from maize supplied with mineral fertilizer. The mineral composition of maize silage, i.e., the content of calcium (Ca) and magnesium (Mg) was modified by fertilization.